The Relationship Between Compliance With Iron Supplement (TTD) Consumption and the Incidence of Anemia Among Adolescent Girls at SMPN 16 Sukabumi City - Rahayu, Reza Gustiana; Andriani, Ria; Novryanthi, Dhinny (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Adherence to blood-boosting tablet consumption among adolescent girls is vital for preventing anemia and maintaining optimal hemoglobin levels to support overall health. Objective: This study aimed to examine the relationship between adherence to blood-boosting tablet consumption and anemia incidence among adolescent girls. Methods: A quantitative cross-sectional study was conducted among 36 randomly selected grade VII students at SMPN 16 Sukabumi City, using the MMAS-8 questionnaire for adherence and the Homovue tool for hemoglobin measurement, analyzed with the Kendall tau test. Results: The findings revealed a significant relationship between adherence and anemia incidence, with a p-value of 0.002 (<0.05). Students with low adherence showed a higher prevalence of anemia, while those with moderate to high adherence maintained normal hemoglobin levels. The results also indicated that knowledge, motivation, and family support influenced adherence behavior. These findings confirm that consistent consumption of blood-boosting tablets effectively reduces anemia risk among adolescents. Conclusion: There is a significant correlation between adherence to blood-boosting tablet intake and anemia prevention, highlighting the importance of continuous education, motivation, and parental involvement to improve adolescent health outcomes.